The complete chloroplast genome sequences of an endemic species of Urticaceae (Debregeasia hekouensis) - Zhao-Yang Sun; Jie Liu; Moses C. Wambulwa; Zhong-Hu Li; Zeng-Yuan Wu (Mitochondrial DNA. Part B. Resources, 2021)
Debregeasia hekouensis, which belongs to the nettle family (Urticaceae), is a local endemic species in Hekou County, Yunnan Province, China. To provide a basis for the development of effective molecular markers for its conservation, we sequenced the chloroplast (cp) genome of D. hekouensis in the present study. The total length of the chloroplast(cp) genome was 155,941 bp, and exhibited a typical quadripartite structure, with a pair of IRs (inverted repeats; 25,664 bp in length) being separated by a small single copy (SSC) region of 19,085 bp and a large single copy (LSC) region of 85,528 bp. The cp genome contained a total of 112 genes, including 78 protein-coding genes, 30 tRNA genes, and 4 rRNA genes. The GC content of the entire cp genome, LSC region, SSC region, and IR region was 36.3%, 34.0%, 29.4%, and 42.7%, respectively. Phylogenetic analysis indicated that D. hekouensis is evolutionarily closer to Debregeasia orientalis and Debregeasia squamata.